Poor news : media discourses of poverty in times of austerity - Harkins, Steven; Lugo-Ocando, Dr. Jairo (Discourse, power, and society., 2017)
Poor News examines the way discourses of poverty are articulated in the news media by incorporating specific narratives and definers that bring about certain ideological worldviews.